Visualization of the sustainability level of crude palm oil production: a life cycle approach - Omran, Najat; Sharaai, Amir Hamzah; Hashim, Ahmad Hariza (MDPI, 2021)
The Malaysian palm oil is an important source of social development and economic growth in the country. Nevertheless, it has been accused of conducting unsustainable practices that may affect the sustainability of this industry. Thus, this study aims to identify the level of sustainability of crude palm oil (CPO) production. Environmental impacts were assessed using the International Organization for Standardization (ISO) standardized life cycle assessment (LCA). Economic impacts were evaluated using life cycle costing (LCC). Social impact assessment was identified based on the UNEP/SETAC Guidelines for social life cycle assessment (S-LCA). Life cycle sustainability assessment (LCSA) was used to combine three methods: LCA, life cycle costing (LCC) and S-LCA using the scoring system method. Finally, a presentation technique was developed to visualize the LCSA results. The results show that crude palm oil production requires more improvement to be a sustainable product. The study feasibly enables the decision-makers to understand the significant environmental, economic, and social hotspots during the crude palm oil production process in order to promote palm oil production.